Global Developmental Gene Programing Involves a Nuclear Form of Fibroblast Growth Factor Receptor-1 (FGFR1). - Christopher Terranova; Sridhar T Narla; Yu-Wei Lee; Jonathan Bard; Abhirath Parikh; Ewa K Stachowiak; Emmanuel S Tzanakakis; Michael J Buck; Barbara Birkaya; Michal K Stachowiak (PLoS ONE, 2015)
Genetic studies have placed the Fgfr1 gene at the top of major ontogenic pathways that enable gastrulation, tissue development and organogenesis. Using genome-wide sequencing and loss and gain of function experiments the present investigation reveals a mechanism that underlies global and direct gene regulation by the nuclear form of FGFR1, ensuring that pluripotent Embryonic Stem Cells differentiate into Neuronal Cells in response to Retinoic Acid. Nuclear FGFR1, both alone and with its partner nuclear receptors RXR and Nur77, targets thousands of active genes and controls the expression of pluripotency, homeobox, neuronal and mesodermal genes. Nuclear FGFR1 targets genes in developmental pathways represented by Wnt/β-catenin, CREB, BMP, the cell cycle and cancer-related TP53 pathway, neuroectodermal and mesodermal programing networks, axonal growth and synaptic plasticity pathways. Nuclear FGFR1 targets the consensus sequences of transcription factors known to engage CREB-binding protein, a common coregulator of transcription and established binding partner of nuclear FGFR1. This investigation reveals the role of nuclear FGFR1 as a global genomic programmer of cell, neural and muscle development.